Intragastric prepyloric enteral nutrition, bolus vs continuous in the adult patient: A systematic review and meta‐analysis. (16th February 2022) - Bolgeo, Tatiana; Di Matteo, Roberta; Gallione, Chiara; Gatti, Denise; Bertolotti, Marinella; Betti, Marta; Roveta, Annalisa; Maconi, Antonio
Abstract: Bolus and continuous nutrition are commonly used enteral nutrition (EN) administration methodologies. Currently, there is insufficient evidence to establish which is the most effective method for reducing gastrointestinal complications in adult patients. The aim of this review is to evaluate the impact of bolus/intermittent EN compared with continuous EN for the following outcomes: diarrhea, constipation, emesis/vomiting, gastric residual volume, aspiration, and glycemic control in adult patients receiving intragastric prepyloric EN in the hospital setting. Bibliographical research was performed on the following databases: PubMed, Embase, CINAHL, and the Cochrane Central Register of Controlled Trials. The review included all randomized and nonrandomized controlled trials of patients aged ≥18 years with preserved gastrointestinal function. Meta‐analysis was performed by Review Manager V.5.3. Seven studies including 551 patients were included in the meta‐analysis. Five of these studies reported that the diarrhea rate was higher in the bolus feeding group (risk ratio [RR] = 2.50; 95% CI, 1.17–5.34; P = 0.02), and another five of these studies indicated that the aspiration rate was higher in the continuous feeding group (RR = 0.55; 95% CI, 0.35–0.87; P = 0.01). There were no significant differences for the other outcomes. In conclusion, intermittent EN appears to reduce the incidence of aspiration in the hospital setting; however, it may increase the risk of diarrhea. For future research, we hypothesize the joint use of continuous nutrition until the patient reaches tolerance and then passing to bolus nutrition, thus reducing the incidence of aspiration and enabling a physiological nutrition intake.